2023
DOI: 10.3847/2041-8213/acba17
|View full text |Cite
|
Sign up to set email alerts
|

The IXPE View of GRB 221009A

Abstract: We present the IXPE observation of GRB 221009A, which includes upper limits on the linear polarization degree of both prompt and afterglow emission in the soft X-ray energy band. GRB 221009A is an exceptionally bright gamma-ray burst (GRB) that reached Earth on 2022 October 9 after traveling through the dust of the Milky Way. The Imaging X-ray Polarimetry Explorer (IXPE) pointed at GRB 221009A on October 11 to observe, for the first time, the 2–8 keV X-ray polarization of a GRB afterglow. We set an upper limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 63 publications
3
23
0
Order By: Relevance
“…These authors reported the discovery of nine dust rings and derived the distances, with the most distant one lying at 3635 ± 36 pc, potentially already beyond the detection range of the RF09 method. Observations with IXPE (Negro et al 2023) confirm the most distant dust ring found by Swift at 3.75 ± 0.0375 kpc and report an even more distant dust curtain at 14.41 ± 0.865 kpc. Recently, Vasilopoulos et al (2023) reported a detailed analysis of Swift XRT data and also found evidence for dust out to 15 kpc (see Williams et al 2023 for further analysis), and XMM-Newton analysis of a total of 20 dust rings presented by Tiengo et al (2023) detects an even further dust curtain at ≈18.6 kpc.…”
Section: Extinction Selectionsupporting
confidence: 57%
See 2 more Smart Citations
“…These authors reported the discovery of nine dust rings and derived the distances, with the most distant one lying at 3635 ± 36 pc, potentially already beyond the detection range of the RF09 method. Observations with IXPE (Negro et al 2023) confirm the most distant dust ring found by Swift at 3.75 ± 0.0375 kpc and report an even more distant dust curtain at 14.41 ± 0.865 kpc. Recently, Vasilopoulos et al (2023) reported a detailed analysis of Swift XRT data and also found evidence for dust out to 15 kpc (see Williams et al 2023 for further analysis), and XMM-Newton analysis of a total of 20 dust rings presented by Tiengo et al (2023) detects an even further dust curtain at ≈18.6 kpc.…”
Section: Extinction Selectionsupporting
confidence: 57%
“…This method results in a significantly lower extinction value (but is only valid out to 2-3 kpc) compared to the SF11 value. Taking into account the existence of dust at larger distances determined by X-ray measurements of dust rings (Negro et al 2023;Williams et al 2023;Vasilopoulos et al 2023), we proceed to discuss the reliability of these measurements and conduct our follow-up analysis using both correction methods for comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We find the total fluence = (9.47 ± 0.07) × 10 −2 erg cm −2 and E γ,iso = (1.01 ± 0.007) × 10 55 erg. Assuming an opening angle of 2° (Negro et al 2023), the beaming corrected energy is = ǵ E 6.1 ( ) q 10 2 j 51 2 erg. We obtain the isotropic-equivalent luminosity by integrating the spectrum in the t 0 + 230.8 s to t 0 + 231.8 s interval.…”
Section: Energeticsmentioning
confidence: 99%
“…, where n 0 is the medium number density, η γ is the radiative efficiency of the prompt phase, and t jet is measured in days. Although extensive multiwavelength follow-up of GRB 221009A did not reveal an apparent achromatic break in the afterglow light curve, a number of θ jet estimates are reported, ranging from 0°.7 to >10°.7 (An et al 2023;Kann et al 2023;Negro et al 2023;O'Connor et al 2023;Williams et al 2023), which, assuming typical η γ = 0.2 and n 0 = 1 cm −3 , imply E K from ∼5 × 10 51 to ∼5 × 10 53 and even higher.…”
Section: Collimation-corrected Energy and Central Enginementioning
confidence: 99%